THỜI ĐIỂM SỬA LỖI TRONG LỚP HỌC NÓI TIẾNG ANH TẠI MỘT TRƯỜNG ĐẠI HỌC VIỆT NAM: QUAN ĐIỂM CỦA GIÁO VIÊN, SINH VIÊN VÀ THỰC TẾ CHỌN THỜI ĐIỂM SỬA LỖI NÓI CỦA GIÁO VIÊN (Journal of Foreign Language Studies, 2022)
This study investigates teachers’ and students’ perspectives and teachers’ practices regarding the timing of oral corrective feedback (OCF) in EFL speaking classes. There has been some research on these issues worldwide, but little research was conducted in Vietnamese higher education context. Data were gathered from five semi-structured interviews with five EFL teachers, classroom observations, and five focus group interviews with 35 first-year Englishmajored students. The findings reveal the consistency and inconsistency between teachers’ perspectives and their actual practices as well as between teachers’ perspectives and students’ preferences for the timing of OCF. On that basis, pedagogical implications are discussed.
Keywords: OCF timing; speaking skill; perspectives